Academic Burnout and Relationship with Gratitude - Friska Yuniar Nindi Pratiwi; Heri Saptadi Ismanto; Leni Iffah (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2023)
In education, academic burnout is a common problem that is often encountered and triggers problems related to student achievement and learning outcomes. High academic burnout is one of the triggers for high academic burnout among students. The aim of this research is, first to test empirically the relation between gratitude and academic burnout, and second to find out whether there or not the differences in academic burnout between male and female students. This research is descriptive correlative research. The number of samples is 197 respondents from the total population and using simple random sampling techniques for sampling. To find the relationship between the two variables, the product-moment correlation formula is used with a 5% of level error, and a t-test to look for the difference in the level of academic burnout between male and female students, the calculation is assisted by the SPSS program. The results of this study are, first, product-moment correlation reported there is a significant negative correlation (r-value = -0,387 > r-table 0,139, p= 0,000) between gratitude and academic burnout. Second, the results from the t-test is, there is no significant difference in academic burnout between male and female students meaning that both male and female students have the same opportunity to experience academic burnout.